Surgical Outcome of Children with a Malignant Liver Tumour in The Netherlands: A Retrospective Consecutive Cohort Study - Merel B. Klunder; Janneke L. M. Bruggink; Leon D. H. Huynh; Frank A. J. A. Bodewes; Alida F. W. van der Steeg; Kathelijne C. J. M. Kraal; C. P. (Kees); Martine van Grotel; József Zsiros; Marc H. W. A. Wijnen; I. Q. (Quintus); Robert J. Porte; et al. (MDPI AG, 2022)
Introduction: Six to eight children are diagnosed with a malignant liver tumour yearly in the Netherlands. The majority of these tumours are hepatoblastoma (HB) and hepatocellular carcinoma (HCC), for which radical resection, often in combination with chemotherapy, is the only curative treatment option. We investigated the surgical outcome of children with a malignant liver tumour in a consecutive cohort in the Netherlands. Methods: In this nationwide, retrospective observational study, all patients (age < 18 years) diagnosed with a malignant liver tumour, who underwent partial liver resection or orthotopic liver transplantation (OLT) between January 2014 and April 2021, were included. Children with a malignant liver tumour who were not eligible for surgery were excluded from the analysis. Data regarding tumour characteristics, diagnostics, treatment, complications and survival were collected. Outcomes included major complications (Clavien-Dindo ≥ 3a) within 90 days and disease-free survival. The results of the HB group were compared to those of a historical HB cohort. Results: Twenty-six children were analysed, of whom fourteen (54%) with HB (median age 21.5 months), ten (38%) with HCC (median age 140 months) and one with sarcoma and a CNSET. Thirteen children with HB (93%) and three children with HCC (30%) received neoadjuvant chemotherapy. Partial hepatic resection was possible in 19 patients (12 HB, 6 HCC, and 1 sarcoma), whilst 7 children required OLT (2 HB, 4 HCC, and 1 CNSET). Radical resection (R0, margin ≥ 1.0 mm) was obtained in 24 out of 26 patients, with recurrence only in the patient with CNSET. The mean follow-up was 39.7 months (HB 40 months, HCC 40 months). Major complications occurred in 9 out of 26 patients (35% in all, 4 of 14, 29% for HB). There was no 30- or 90-day mortality, with disease-free survival after surgery of 100% for HB and 80% for HCC, respectively. Results showed a tendency towards a better outcome compared to the historic cohort, but numbers were too small to reach significance. Conclusion: Survival after surgical treatment for malignant liver tumours in the Netherlands is excellent. Severe surgical complications arise in one-third of patients, but most resolve without long-term sequelae and have no impact on long-term survival.